The Impact of Green Accounting Requirements on the E-Accounting Activities of Employees at Al-Itihad Food Industries Company Limited in Babylon Governorate - Nadhim Khasran Hassooni al-Shaibani (International Forum of Researchers and Lecturers, 2025)
The purpose of the current research is to identify the impact of green accounting represented by (activating the accounting system to keep pace with environmental activities (GAKE), Activating the environmental activity measurement system (GAAM), Activating the environmental cost analysis system (GACO), activating the reporting and disclosure system for sustainable environmental performance (GASD)) on electronic accounting activities represented by (system quality, information quality, and service quality) among employees of Al-Ittihad Company for Food Industries Limited in Babil Governorate. This purpose was derived from a main problem that the research sought to achieve, which was (Is there an impact of green accounting requirements on electronic accounting activities at Al-Ittihad Company for Food Industries Limited in Babil Governorate?), for which two hypotheses were developed to address this problem. Therefore, to identify the means to address the research problem, a questionnaire tool was adopted to collect the necessary data for analysis. As (150) questionnaires were distributed, and (142) questionnaires were retrieved by (3) questionnaires, including damaged ones, and (139) questionnaires were valid for analysis, using the program (SPSS & AMOS) data was interpreted and analysed by extracting (mean, standard deviation, stability coefficient, correlation between variables, impact and interpretation coefficient). On the basis of the interpretation and analysis process, the research reached several results, the most important of which is that there is a significant correlation and impact between green accounting requirements and electronic accounting activities. This indicates that by integrating green accounting requirements into the electronic accounting system, companies can accurately measure and evaluate the impact of their activities on the environment. This helps identify areas that need to be improved and helps minimize negative impacts.